Research status of gas sensing performance of MoTe2-based gas sensors: A mini review - Wang, Jingyu; Zeng, Wen; Zhou, Qu (Frontiers in Chemistry, 2022)
Transition metal dichalcogenides (TMDs) have been widely explored for their excellent gas sensing properties, especially high sensitivity and stability at room temperature. MoTe2 exhibits good sensitivity and selectivity to some nitrogen-containing gases (i.e., NO2, NH3) and has received extensive attention in gas sensing. In addition, increasingly complex production environments place demands on high-quality gas sensors. Therefore, worldwide efforts are devoted to designing and manufacturing MoTe2-based gas sensors with faster response and recovery speed. This paper summarizes the research progress of MoTe2-based gas sensing, focuses on the practical measures to improve the response and recovery speed of MoTe2-based sensors, and discusses the mechanism. This provides guidance for exploring higher performance MoTe2 sensors